2010
DOI: 10.1002/cyto.b.20575
|View full text |Cite
|
Sign up to set email alerts
|

Cellular features of psoriatic skin: Imaging and quantification using in vivo reflectance confocal microscopy

Abstract: Background: In vivo reflectance confocal microscopy (RCM) is a novel, exciting imaging technique. It provides images of cell-and tissue structures and dynamics in situ, in real time, without the need for ex vivo tissue samples. RCM visualizes the superficial part of human skin up to a depth of 250 lm. In psoriasis, an erythematosquamous skin disease, we evaluated well known histological features of stable psoriasis vulgaris (PP) with RCM. RCM images were correlated to morphological and cell biological findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 25 publications
2
63
2
3
Order By: Relevance
“…Currently, RCM has the best resolution, albeit at the cost of a very limited depth of imaging. In consequence, RCM criteria for a number of diagnoses have been established comparing the method with histology [26, 14–17, 19, 20, 22, 23, 25, 26]. HD-OCT is a promising high-resolution imaging technique which offers comparable resolution to RCM and improved penetration [9–11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, RCM has the best resolution, albeit at the cost of a very limited depth of imaging. In consequence, RCM criteria for a number of diagnoses have been established comparing the method with histology [26, 14–17, 19, 20, 22, 23, 25, 26]. HD-OCT is a promising high-resolution imaging technique which offers comparable resolution to RCM and improved penetration [9–11].…”
Section: Discussionmentioning
confidence: 99%
“…One of the restrictions of RCM in evaluating inflammatory skin diseases is the limited penetration depth [26, 14–17, 19, 20, 22, 23, 25, 26]. With HD-OCT not only the visualization and assessment of individual cells but also microanatomic structures can be performed to a depth of 570 μm.…”
Section: Discussionmentioning
confidence: 99%
“…Further, well-established histological features of psoriasis and other inflammatory skin lesions can be visualized with this technique, including characteristic PMN accumulations. It has been shown that these RCM images correlated highly with histology (27)(28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 94%
“…CRM is a valuable tool to evaluate histological features of psoriasis (Figure 18), and the findings correlate with histology [97][98][99].…”
Section: Crm and Other Skin Diseasesmentioning
confidence: 99%